The use and impacts of direct-to-consumer genetic testing for adults with an adoption or out-of-home care experience: A scoping review - Conrick, Jeanette (Jenny); Prictor, Megan; Zarine, Dilshad; Hampson, Ralph (Adoption & fostering, 2025)
Direct-to-consumer genetic testing (DTC-GT), provided by commercial DNA companies, is now widely used across the world to learn more about family history and origins. What has not been explored at any length is the use and impacts of this technology by those who have adoption or out-of-home care (OOHC) experience. The purpose of this scoping review was to explore the use and outcomes of DTC-GT for adults from these communities, in preparation for an Australian research study. Eleven peer-reviewed articles and nine grey literature documents, written in English and published between 2000 and 2023, were located and thematically analysed. Findings suggest that DTC-GT testing can provide more information about health and heritage and offer the opportunity for connection with biological family members, whilst also raising personal challenges to do with adoption or OOHC status. DTC-GT also raises questions about the impacts of the public sharing of information, the ownership and future uses of genetic material and the support needs of the users of this technology. Plain language summary Genetic testing, provided by commercial DNA companies, is now widely used across the world to learn more about family history and origins. What has not been explored at any length is the use and impacts of this technology for those who have adoption or out-of-home care (OOHC) experience. This review of the literature was conducted to understand the reasons, the outcomes and impacts of using direct-to-consumer genetic testing (DTC-GT) and data platforms by those with adoption or out-of-home care experience and to prepare for an Australian research study exploring the use and outcomes of commercially available genetic testing for adults from these communities. Twenty documents, written in English and published between 2000 and 2023, were located and analysed. Findings suggest that genetic testing can provide more information about health and heritage and offer the opportunity for connection with biological family members. The review also highlighted that for those with adoption or OOHC experience, information can impact personal identity and a sense of belonging and prompt a re-emergence of grief. In addition, the review suggested that DTC-GT raises dilemmas about the ownership of genetic material, the public sharing and future uses of genetic information, highlighting the need for increased regulation and support for consumers.